Planning Weir Jeruk Gulung In Troso Village, Pecangaan district, Jepara Regency - Ikhwanudin, Ikhwanudin (Science and Technology Research Centre, Universitas PGRI Semarang, 2021)
Lack of water availability for agricultural land during the dry season results in less optimal agricultural productivity, This is what happened in Troso Lor village, Pecangaan sub-district, Jepara Regency. In order to meet water needs continuously and maintain the availability of water sources, efforts are needed in the framework of protecting, developing, controlling and utilizing water resources. Â For this reason, a construction plan for the Jeruk Gulung Dam on the Jeruk Gulung River will be planned as an effort to utilize water sources for irrigation in the Troso village area, Pecangaan sub-district, Jepara regency. Â Meanwhile, the results of the analysis of irrigation water requirements are used for channel hydrological analysis. After planning the weir construction, the weir stability control is carried out against rolling, shear, eccentricity and soil bearing capacity . Meanwhile, the results of the analysis of irrigation water requirements are used for channel hydrological analysis. After planning the weir construction, the weir stability control is carried out against rolling, shear, eccentricity and soil bearing. Based on the results of the analysis and planning of the Jeruk Gulung Dam, the data obtained for the area of rice fields is 16 Ha with a requirement of 0.019 m3 / s of irrigation water with a fixed weir type with 100.1347 m3 / sec flood discharge. The width of the weir is 19.2 m with an effective width of 17.7 m and a width of 1 m for rinsing.